Pengaruh Pendidikan Akhlak dan Pembinaan Sholat terhadap Pembentukan Karakter Eks Wanita Tuna Susila - Fitrotun Rahmawati; A. Dardiri Hasyim (Fahima, 2023)
This study aims 1) to find out how the influence of moral education on the character formation of former prostitutes, 2). To find out how the influence of prayer coaching on the character formation of former prostitutes, 3). This study aims to determine the effect of moral education and moral development on character building for former prostitutes at the "Wanodyatama" Surakarta Women's Social Service Institution in 2022. This research is a type of quantitative research at the Women's Social Service Institution "Wanodyatama" Surakarta. This research was conducted from February to March 2022. The subjects of this study were 100% of the 67 former prostitutes as research respondents. Data were taken through questionnaires with validity and reliability tests. The research data were analyzed by multiple regression techniques. The results of this study indicate that: There is a significant effect of moral education on the formation of the character of ex-prostitutes, There, is a significant influence of prayer development on the formation of the character of ex-prostitutes, and There is a significant influence of moral education and prayer development on the formation of the character of ex-prostitutes in the orphanage. Women's Social Services "Wanodyatama" Surakarta in 2022. Based on the results of this study, it is recommended for the head of the orphanage maximize activities that are not yet optimal and develop methods of religious development that already exist.